Integration and trade diversion. - BAUMANN, Renato (1993)
Gives a brief description of each of four integration processes, viz. MERCOSUR, Andean Pact, CACM and CARICOM and presents basic data on pre-integration trade flows. Estimates by simulation the creation of new trade flows and the diversion of trade for the four integration processes.